2013
DOI: 10.5999/aps.2013.40.5.496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amniotic Fluid Stem Cells and Amniotic Fluid Cells on the Wound Healing Process in a White Rat Model

Abstract: BackgroundAmniotic-fluid-derived stem cells and amniocytes have recently been determined to have wound healing effects, but their mechanism is not yet clearly understood. In this study, the effects of amniotic fluid stem cells and amniocytes on wound healing were investigated through animal experiments.MethodsOn the back of Sprague-Dawley rats, four circular full-thickness skin wounds 2 cm in diameter were created. The wounds were classified into the following four types: a control group using Tegaderm disc wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…This result suggested that CD117-positive cells exhibited mesenchymal characteristics. Moreover, consistent with our results, other studies reported that hAFS cells can express the stem cell markers CD13, CD29, CD44, CD73, CD90, CD105 and CD117 (Davydova et al, 2009;Wouters et al, 2007;Yang et al, 2013;Zagoura et al, 2013). Additionally, we found that CD117-positive hAFS cells expressed the transcription factor OCT4, which works as a key factor in the transcriptional network to govern pluripotency and self-renewal of ESCs.…”
Section: Discussionsupporting
confidence: 94%
“…This result suggested that CD117-positive cells exhibited mesenchymal characteristics. Moreover, consistent with our results, other studies reported that hAFS cells can express the stem cell markers CD13, CD29, CD44, CD73, CD90, CD105 and CD117 (Davydova et al, 2009;Wouters et al, 2007;Yang et al, 2013;Zagoura et al, 2013). Additionally, we found that CD117-positive hAFS cells expressed the transcription factor OCT4, which works as a key factor in the transcriptional network to govern pluripotency and self-renewal of ESCs.…”
Section: Discussionsupporting
confidence: 94%
“…MSCs have great potential in the fields of tissue engineering and regenerative medicine [38]. Recent studies have focused on the effect of reducing oxygen tension (hypoxia) on the behavior and functions of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that adipose-derived stem cell therapy was used to treat nasal skin necrosis, and satisfactory results of healing were obtained. 34 , 35 , 36 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%